Strategi Pencegahan Anemia pada Ibu Hamil melalui Layanan Posyandu - Maliha Amin; Michelle Salsabilah; M. Iqbal Pratama; Marsha Salsabila; M. Dwi Satria; Bella Regita Az-Zahra (Universitas Muhammadiyah Manado, 2024)
Anemia in pregnant women is a serious health problem in Indonesia, with a prevalence of 48.9% based on the 2018 Riskesdas data. This condition can have negative impacts on the health of both the mother and the fetus, such as increased risks of premature birth, low birth weight babies, and maternal and infant mortality. Anemia in pregnant women is generally caused by deficiencies in iron, folic acid, and vitamin B12. This community service activity aims to educate the public about preventing anemia among pregnant women, conducted at the Dahlia Posyandu in the working area of Puskesmas Ariodillah Palembang. The activities include outreach on the signs, symptoms, causes, and prevention of anemia, as well as hemoglobin (Hb) level examinations for early detection of anemia. The methods used are interactive socialization and health examinations, involving posyandu cadres and the surrounding community. The examination results indicate that no pregnant women were found to be anemic, and participants’ knowledge of anemia increased by 95% after attending the outreach. This activity is expected to raise public awareness of the importance of anemia prevention and health during pregnancy. Recommendations for follow-up programs include ongoing education, improving access to health services, and attention to the health of the elderly in the area.